Health Policy and Analytical Cross-Sectional Study of Tuberculosis Determinants Knowledge Nutrition Housing Density Factors Community - Nurnia Saraun; La Ode Asrianto; Teti Susliyanti; Sarifudin Andi Latif (JAKESPOL Journal of Health Policy Analysis, 2026)
Introduction: Tuberculosis (TB) remains a major public health concern globally and in Indonesia, with increasing incidence reported in recent years. Multiple determinants, including individual knowledge, nutritional status, and housing density, contribute to TB transmission dynamics. In the context of health policy and community-based prevention, understanding these determinants is essential to inform targeted interventions. This study aimed to analyze the association between knowledge, nutritional status, and housing density with pulmonary tuberculosis incidence in the working area of UPTD Puskesmas Lapandewa, South Buton Regency. Methods: This study employed an analytical observational design with a cross-sectional approach. The population consisted of 132 suspected TB patients registered in 2025, with a sample of 99 respondents selected using simple random sampling. Data were collected through structured questionnaires and anthropometric measurements. Variables included knowledge, housing density, nutritional status, and TB incidence. Data were analyzed using chi-square tests to assess associations, with a significance level of 0.05. Effect sizes were estimated using Odds Ratios (OR) with 95% Confidence Intervals (CI). Results: Low knowledge was significantly associated with TB incidence (OR=3.12; 95% CI: 1.45–6.72; p=0.003). High housing density was also significantly related to TB occurrence (OR=2.87; 95% CI: 1.36–6.05; p=0.005). Respondents with poor nutritional status had a higher risk of TB (OR=3.45; 95% CI: 1.68–7.10; p=0.001). These results indicate that behavioral and environmental determinants play a critical role in TB transmission. Conclusion: Knowledge, housing density, and nutritional status are significant determinants of pulmonary tuberculosis incidence. Strengthening health policies that focus on community education, housing improvements, and nutritional interventions is essential to reducing the TB burden. Integrated public health strategies are recommended to enhance early detection and prevention efforts.